An epigenetic map of age-associated autosomal loci in northern European families at high risk for the metabolic syndrome - Ali, Omar; Cerjak, Diana; Kent, Jack W; James, Roland; Blangero, John; Carless, Melanie A; Zhang, Yi (Clinical epigenetics, 2015)
Background The prevalence of chronic diseases such as cancer, type 2 diabetes, metabolic syndrome (MetS), and cardiovascular disease increases with age in all populations. Epigenetic features are hypothesized to play important roles in the pathophysiology of age-associated diseases, but a map of these markers is lacking. We searched for genome-wide age-associated methylation signatures in peripheral blood of individuals at high risks for MetS by profiling 485,000 CpG sites in 192 individuals of Northern European ancestry using the Illumina HM450 array. Subjects (ages 6–85 years) were part of seven extended families, and 73% of adults and 32% of children were overweight or obese. Results We found 22,122 genome-wide significant age-associated CpG sites ( P α=0.05 = 3.65 × 10 −7 after correction for multiple testing) of which 14,155 are positively associated with age while 7,967 are negatively associated. By applying a positional density-based clustering algorithm, we generated a map of epigenetic ‘hot-spots’ of age-associated genomic segments, which include 290 age-associated differentially methylated CpG clusters (aDMCs), of which 207 are positively associated with age. Gene/pathway enrichment analyses were performed on these clusters using FatiGO. Genes localized to both the positively ( n = 241) and negatively ( n = 16) age-associated clusters are significantly enriched in specific KEGG pathways and GO terms. The most significantly enriched pathways are the hedgehog signaling pathway (adjusted P = 3.96 × 10 −3 ) and maturity-onset diabetes of the young (MODY) (adjusted P = 6.26 × 10 −3 ) in the positive aDMCs and type I diabetes mellitus (adjusted P = 3.69 × 10 −7 ) in the negative aDMCs. We also identified several epigenetic loci whose age-associated change rates differ between subjects diagnosed with MetS and those without. Conclusion We conclude that in a family cohort at high risk for MetS, age-associated epigenetic features enrich in biological pathways important for determining the fate of fat cells and for insulin production. We also observe that several genes known to be related to MetS show differential epigenetic response to age in individuals with and without MetS.